2015
DOI: 10.17275/per.15.spi.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Virtual Reality Studies in Foreign Language Education

Abstract: The use of Virtual Reality in education has been highly prevalent in recent years. In nearly every domain of education, integration of Virtual Reality has been ongoing including foreign language teaching and learning. There is a huge shift in teaching and learning facilities from conventional classrooms to interactive ones. What makes Virtual Reality special in comparison to other technologies are immersion, interaction and involvement properties. Therefore, the purpose of this study was to analyze the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 12 publications
8
36
1
Order By: Relevance
“…Past reports of ELT research trends by İnal et al (2016), Solak (2014), and Yağız et al (2016) had likewise demonstrated that for practical reasons, using surveys -especially Likert type scales -was the primary mode of data collection in the Turkish EFL context. The absence of an ideal sample size was another shared finding of the current analysis, but the choice over primary and secondary students as sample groups was unaccustomed in previous reviews of ELT research in Turkey, where there was a tendency to study adult groups, i.e.…”
Section: Distribution Of Graduate Theses According To Data Collectionmentioning
confidence: 97%
See 4 more Smart Citations
“…Past reports of ELT research trends by İnal et al (2016), Solak (2014), and Yağız et al (2016) had likewise demonstrated that for practical reasons, using surveys -especially Likert type scales -was the primary mode of data collection in the Turkish EFL context. The absence of an ideal sample size was another shared finding of the current analysis, but the choice over primary and secondary students as sample groups was unaccustomed in previous reviews of ELT research in Turkey, where there was a tendency to study adult groups, i.e.…”
Section: Distribution Of Graduate Theses According To Data Collectionmentioning
confidence: 97%
“…The absence of an ideal sample size was another shared finding of the current analysis, but the choice over primary and secondary students as sample groups was unaccustomed in previous reviews of ELT research in Turkey, where there was a tendency to study adult groups, i.e. undergraduate students (İnal et al, 2016;Solak, 2014;Yağız et al, 2016).…”
Section: Distribution Of Graduate Theses According To Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations